2020
DOI: 10.4103/meajo.meajo_177_20
|View full text |Cite
|
Sign up to set email alerts
|

Foveal congenital simple hamartoma of retinal pigment epithelium: A report of two cases

Abstract: We report two cases with foveal congenital simple hamartoma of the retinal pigment epithelium (CSHRPE), as both patients presented to our retina services complaining of a unilateral decreased vision. Full ophthalmic examination and multimodal imaging were performed including fundus photography, fundus autofluorescence, optical coherence tomography, fluorescein angiography, and electrophysiological testing. Both patients presented with 20/80 vision in the affected eyes. Foveal CSHRPE was found in both eyes, alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Shields et al reported associated features in a series of five cases of CSHRPE [ 2 ], including minimally dilated retinal feeding arteries and draining retinal veins (100%), mild adjacent retinal traction (80%), retinal exudation (20%), and vitreous pigmented cells (20%). Additionally, Badawi et al documented a case of CSHRPE with a solitary tumor associated with multiple posterior pole small hyperpigmented lesions and peripheral hypopigmented lesions indicating RPE atrophy [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shields et al reported associated features in a series of five cases of CSHRPE [ 2 ], including minimally dilated retinal feeding arteries and draining retinal veins (100%), mild adjacent retinal traction (80%), retinal exudation (20%), and vitreous pigmented cells (20%). Additionally, Badawi et al documented a case of CSHRPE with a solitary tumor associated with multiple posterior pole small hyperpigmented lesions and peripheral hypopigmented lesions indicating RPE atrophy [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rarity of CSHRPE, along with its asymptomatic nature, particularly in patients with a history of trauma, pigmentary variations [ 4 , 14 ], or exposure to Toxoplasma gondii parasite or other infectious diseases complicates its accurate diagnosis during the initial evaluation. However, advanced imaging modalities play a crucial role in differentiation, offering valuable insights into the structural aspects of CSHRPE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation